THE INFLUENCE OF TEACHER'S TEACHING STYLE AND LEARNING DISCIPLINE ON STUDENTS' COGNITIVE ABILITY AT SMP NEGERI 3 MOTOLING TIMUR - Joubert M. Dame; Herman Dolonseda; Agsel Lendongan (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2023)
This study aims to determine the effect of the teacher's teaching style and learning discipline on the cognitive abilities of students at SMP Negeri 3 Motoling Timur. This test strategy is a learning technique with an example of 75 individuals. The procedure used in collecting information is a survey strategy (poll) and documentation. The results of the examination were dissected using various recurrence direct examinations, basic connection examinations and various connection examinations. The results showed: (1) There is an influence between the Teacher's Teaching Style on the Cognitive Ability of students of SMP Negeri 3 Motoling Timur by 44.89% with t count > t table = 7.71 > 2.04 and F count > F table. Keywords: Teacher's Teaching Style, Learning Discipline, Students' Cognitive Ability